2017
DOI: 10.5586/am.1094
|View full text |Cite
|
Sign up to set email alerts
|

Two species of true morels (the genus Morchella, Ascomycota) recorded in the Ojców National Park (south Poland)

Abstract: In this paper, we present results of survey on the occurrence of true morels, conducted in the Ojców National Park (ONP). The first data about true morels from the area of the ONP date back to the nineteenth century. However, despite multiple surveys in the next decades, their presence has not been confirmed. Therefore, true morels were thought to be extinct in the ONP. In 2014 and 2015, two morphotypes of true morel fruiting bodies were discovered in two sites, identified as black morels and yellow morels. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Other authors (Taşkın et al 2010, 2012; Clowez 2012) mainly reported associations with conifers ( L. decidua , Piceaabies , Pinus sp. ), while Baran and Boroń (2017) also observed Abiesalba , Tiliaplatyphyllos , Acerpseudoplatanus , and Euonymusverrucosa at the localities where M.deliciosa was collected.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Other authors (Taşkın et al 2010, 2012; Clowez 2012) mainly reported associations with conifers ( L. decidua , Piceaabies , Pinus sp. ), while Baran and Boroń (2017) also observed Abiesalba , Tiliaplatyphyllos , Acerpseudoplatanus , and Euonymusverrucosa at the localities where M.deliciosa was collected.…”
Section: Discussionmentioning
confidence: 75%
“…Our results confirm this treatment unambiguously. Mel-13 has so far only been reported from Asia (China, India, and Turkey; O’Donnell et al 2011; Du et al 2012a; Taşkın et al 2012; Richard et al 2015), while Mel-26 has, in addition to Turkey (Taşkın et al 2010, 2012), also been reported from some European countries (France, Poland, and Sweden; Clowez 2012, as several varieties of M.conica ; Taşkın et al 2012; Richard et al 2015; Baran and Boroń 2017). The Czech specimens that were examined were collected in mid-April in mixed forests, mainly under Fraxinusexcelsior , Picea sp., and Pinus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, there are 56, 64, and 92 individuals were collected from high, low, and middle latitudes of the northeastern, central-eastern, and southwestern in the QTPs, respectively. Micromorphological data were obtained from the dried specimens and observed under a light microscope following Baran and Boroń (2017) . Voucher specimens were deposited in Extreme Environment Microbiology Laboratory, Qinghai University, Xining, China.…”
Section: Methodsmentioning
confidence: 99%
“…Among the different culture media, the morphology which is considered as typical for morel mycelia (He et al 2015 ) was observed in MEA, MEA-lactose and MEA-coconut cultures. Baran and Boron ( 2017 ) characterized the morphology of M. deliciosa and M. esculenta , but the differences between both strains were barely visible. Herein, evident morphological differences among wild morel strains enrich the knowledge about the variation of morel mycelia depending on the culture media composition or isolates.…”
Section: Discussionmentioning
confidence: 99%